Energy prioritization and neurometabolic scaling in a social insect brain - Zach N. Coto; Dajia Ye; Sara Arganda; Jon F. Harrison; James F. A. Traniello (Proceedings of the National Academy of Sciences, 2026)
Brains are metabolically costly and due to their high energetic demands may receive priority under conditions of reduced energy availability. Such preferential energy allocation to the brain has been described for humans and other mammals, but previous studies have not directly quantified brain metabolic rate or simultaneously considered whole-body metabolism. We recorded brain metabolic rate ex vivo, brain mass, body mass, and whole-body metabolic rate in workers of the ant Tetramorium immigrans and found the proportion of whole-body energy allocated to the brain nearly doubled to 45% when nutritionally stressed. Body metabolic rate was significantly reduced without a comparable decrease in brain metabolic rate. The ability of nutritionally compromised workers to recognize and aggressively respond to a sympatric competitor was not affected, indicating that sensory perception and neural processing necessary for this critical behavior are maintained during energy limitation. Our finding that similar patterns of brain energy prioritization occur across remotely related clades with exceptionally different body sizes, respiratory systems, and brain allometries suggests conservation of ancient neurohormonal mechanisms or functional convergence of processes to protect the brain. Furthermore, although the worker brain was 5% of body mass, brain metabolic rate was 24 to 30% of body metabolic rate under unstressed conditions, remarkably similar to the pattern of humans and other mammals. Brain metabolic rate of T. immigrans was predictable from the scaling of brain metabolic rate in mammals, suggesting ecological, physiological, and evolutionary effects of body size on brain metabolic rate are common.